2017
DOI: 10.1002/joc.5372
|View full text |Cite
|
Sign up to set email alerts
|

Possible impacts of a changing climate on intense Ligurian Sea rainfall events

Abstract: Intense rainfall events occasionally occur in northwestern Italy near the Ligurian Sea, especially in autumn when persistent convergence zones trigger thunderstorm systems. Output from EXPRESS‐Hydro simulations of past and future climate suggest that although the number of strong convergence events stays constant in a warming climate, the area of heavy rainfall in the events and duration (shown here as average number of grid points receiving more than 25 mm of rain in a 3‐h period per month) both increase sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Our results confirm therefore the results presented by other authors for Italy and we can conclude that also in the study region yearly 1-day maxima records do not give evidence of any significant trend. It is also worth noticing that a recent study on precipitation output from 12-km horizontal grid spacing EXPRESS-Hydro simulations of past and future climate applied to an area including the points with highest values in figure 2f gives evidence that peak three-hourly rainfall does not increase form 1979-2005 to 2023-2049 periods, even if future events are expected to have a larger areal coverage and a longer duration (Gallus et al, 2017).…”
Section: -Day Annual Maxima Trend Analysismentioning
confidence: 97%
“…Our results confirm therefore the results presented by other authors for Italy and we can conclude that also in the study region yearly 1-day maxima records do not give evidence of any significant trend. It is also worth noticing that a recent study on precipitation output from 12-km horizontal grid spacing EXPRESS-Hydro simulations of past and future climate applied to an area including the points with highest values in figure 2f gives evidence that peak three-hourly rainfall does not increase form 1979-2005 to 2023-2049 periods, even if future events are expected to have a larger areal coverage and a longer duration (Gallus et al, 2017).…”
Section: -Day Annual Maxima Trend Analysismentioning
confidence: 97%
“…More specifically, Crisci et al (2002), Arnone et al (2013), Saidi et al (2015), and Uboldi and Lussana (2018) have found general increasing trends for short-duration rainfall, respectively, in Tuscany, Sicily, Piedmont, and Lombardy regions, while Caloiero et al (2011) have found decreasing trends in Calabria. Finally, Cifrodelli et al (2015) and Gallus et al (2018) have found that trends are not significant in Umbria and Liguria regions, respectively. As no more than 9% of the Italian area was considered in the above studies, it is no wonder that the limited spatial scale could justify the lack of uniformity of the outcomes.…”
Section: Introductionmentioning
confidence: 96%
“…The selected case study corresponds to a back-building MCS; these are among the most important flash-flood producing storms in the Liguria region area [2,4,41] and other Mediterranean coastal regions, such as southern France [3,42] and eastern Spain [43,44]. MCSs are known to have been common in these areas also in the past [45] and there is evidence that climate change could increase their frequency [46]. It is also known that their dynamics generally develop over the sea [42,47], which can control the rainfall intensity by modifying the atmospheric stability according to the average value of sea surface temperature [48][49][50], and can influence the low-level wind field by means of the differential thermal forcing due to sea surface temperature gradients [51,52].…”
Section: Case Study Descriptionmentioning
confidence: 99%